New Cryptocurrency Regulation in Lithuania and the European Union - Laucius, Gediminas (Teisė, 2023)
The paper examines the major threats and related legal challenges posed by activities based on blockchain technology, such as cryptocurrencies, smart contracts, Decentralised Autonomous Organisations (DAOs), the Decentralised Finance System (DeFi), and Non-Fungible Tokens (NFTs). In the light of practical findings, the provisions of the Lithuanian Law on prevention of money laundering and terrorist financing and MiCA regulation are being analysed. The paper arrives at the conclusion that the new national law should effectively contribute to the prevention of cybercrimes, money laundering, terrorist financing, and violation of international sanctions. Nevertheless, a number of other issues typical for cryptocurrencies and other forms of utilisation of the blockchain technology remain unaddressed. Certain loopholes will be partly filled in by MiCA regulation. However, it will not create the required scope of legal certainty for other than cryptocurrencies forms of technology utilisation. On the basis of these findings, the paper puts forward proposals for the further development of the regulation of activities based on the blockchain technology.